Ethno-Religious Voting Pattern and Governance in the Post-2015 Presidential Election in Nigeria - Joy Nkiru Agbo; Kelechi Elijah Nnamani; Christian Ikechukwu Nnadi (Unisia, 2021)
This study therefore examined the link between the ethno-religious voting pattern in the 2015 presidential elections and governance in the post-election era in Nigeria. We anchored our analysis on the Rational Choice Theory and relied on documentary method where data were systematically gleaned from journal articles, newspapers, official documents and other online materials while utilizing content analysis as our analytical compass. Based on this, we hypothesized as follow: the ethno-religious voting pattern in the 2015 presidential election has affected political development of Nigeria under the Buhari administration; the regionalization of political appointments by Buhari administration has increased ethno-regional agitations in Nigeria. On this note, the study found that ethno-religious voting pattern played vital role in determining the pace of governance and how resources should be distributed among the competing ethnic nationalities in the post-election era. It is however, recommended that the electorates should embrace party ideology and competence of candidate as the guiding factor for voting in the future elections to be held in Nigeria.